Exploring the therapeutic potency of cryptotanshinone in cervical cancer: a multi-omics and network pharmacology approach - Lu, Zenghong; Zhu, Gangfeng; Feng, Xiaofei; Xiang, Yi; Chen, Cixiang; Yuan, Huiting; Chen, Zhixing (Frontiers in Genetics, 2024)
IntroductionCervical cancer remains a significant challenge in oncology with an escalating demand for novel therapeutic strategies that can navigate the complexities of its pathophysiology. This study elucidated the antineoplastic effects of cryptotanshinone, a derivative of danshen (Salvia miltiorrhiza), a herb widely utilized in traditional Chinese medicine practices.MethodsEmploying a comprehensive multi-omics approach, including transcriptomic, proteomic, and bioinformatics analyses, we investigated the potential effects of cryptotanshinone on cervical cancer through data mining and computational analysis.Results and DiscussionOur results demonstrated that the potential of cryptotanshinone to disrupted cancer cell proliferation and induced apoptosis may be ascribed to its modulation of gene expression and interaction with specific protein networks. Furthermore, network pharmacology and pathway enrichment analyses identified critical hubs and signaling pathways, suggesting a multi-targeted mechanism of action. Furthermore, the establishment of a prognostic model, which is founded upon differentially expressed genes linked to cryptotanshinone treatment, underscores its promising role as both a prognostic biomarker and a therapeutic agent. These insights pave the way for the integration of cryptotanshinone into therapeutic regimens, offering a promising avenue for enhancing the efficacy of cervical cancer treatment and patient outcomes.